Adherence to drug therapy in diabetic elderly - Borba, Anna Karla de Oliveira Tito (2013)
Sectional and observational study, which investigates access to medicine, socioeconomic and demographic profiles and their association with drug adherence to drug therapy in diabetic elderly assisted in a gerontogeriatric public service. Data were collected from 126 participants through structured interviews between February and September 2011. The results reveal that 47.6% of the elderly received their drug from the public health system.  The elderly women prevailed, in more than 9 years of studies, retired and income of 1-2 minimum wages. As for drug adherence, 93.7% reported using their medication regularly, but only 52.4% were considered compliant under the Test of Batalha. There was no association between socioeconomic and demographic variables and self-reported adherence. It is necessary to invest in educational initiatives targeted to the elderly patients to promote adherence to therapy. DOI:https://doi.org/10.15253/2175-6783.20130002000018